2017
DOI: 10.1080/15564886.2017.1383332
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and Differences in Victimization Risk Factors for Nonoffending and Offending Substance Users

Abstract: In this cross-sectional study of substance users in Norway, we describe the patterns of victimization and investigate the factors associated with victimization, for non-offenders and offenders separately. Recent victimization was reported by 59%, and the victimization-rate was higher among offenders compared to non-offenders (69% and 43%, p<0.001). Women, regardless of offender status, experienced more victimization. Unstable housing was associated with victimization among non-offenders, while markers for more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
2
4
0
Order By: Relevance
“…Our finding on the association between past year psychiatric care and victimization is in parallel with other studies that show a link between mental health problems, SUD, and violent victimization (Azimi & Daigle, 2017;Dean et al, 2018;Hart et al, 2012;Teplin et al, 2005), and shows that mental health problems may mediate the association between SUD and victimization (DiBello et al, 2017). Journal of Interpersonal Violence In this study, the association between being a woman and experiencing violent victimization is similar to previous studies which have documented that women in general are more likely to experience violent victimization (Devries et al, 2014;Isom Scott, 2018;Skjaervø et al, 2018). A recent Danish national report documented that women are victims of physical and psychological intimate-partner violence, stalking, and online harassment more often than men, and that the violence they experience is often more severe.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our finding on the association between past year psychiatric care and victimization is in parallel with other studies that show a link between mental health problems, SUD, and violent victimization (Azimi & Daigle, 2017;Dean et al, 2018;Hart et al, 2012;Teplin et al, 2005), and shows that mental health problems may mediate the association between SUD and victimization (DiBello et al, 2017). Journal of Interpersonal Violence In this study, the association between being a woman and experiencing violent victimization is similar to previous studies which have documented that women in general are more likely to experience violent victimization (Devries et al, 2014;Isom Scott, 2018;Skjaervø et al, 2018). A recent Danish national report documented that women are victims of physical and psychological intimate-partner violence, stalking, and online harassment more often than men, and that the violence they experience is often more severe.…”
Section: Discussionsupporting
confidence: 90%
“…Across studies it was established that common factors that are robustly associated with victimization include risky lifestyles (Engström, 2018; Zaykowski et al, 2019), alcohol and drug use (Johnson et al, 2017; Kuhns & Clodfelter, 2009; Teasdale, 2009), conviction and victimization (Abramsky et al, 2011; de Vries et al, 2019; Spencer et al, 2019), psychiatric symptom and mental illness (Choe et al, 2008; Dean et al, 2018), lower levels of income, living in urban areas, and being separated or divorced (Vaughn et al, 2010), and female gender (Roy et al, 2014; Skjærvø et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Past research has indicated that low self-control is predictive of substance use. The strain canon of criminology is also relevant for understanding more specific stimulant use, as exposure to violence has been identified as a robust risk factor for illicit stimulant use (Lopez-Patton et al 2016; Skjærvø, Clausen, Skurtveit, Abel, & Bukten, 2018; Whiteside et al, 2015). Also consistent with the strain school of criminology, depressive symptoms that stem from such exposures to violence have been identified as a risk factor for illicit stimulant use (Lopez-Patton et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to violence: Previous exposure to violence was also associated with reporting mental distress at baseline (paper I). Mental distress has previously been associated with victimization among substance users and criminal offenders (218,219). Longitudinal studies have reported a bidirectional explanation of this relationship, where victimization could lead to increased mental distress and additionally that mental distress could increase vulnerability and increase the risk of future victimization (219).…”
Section: Substance Usementioning
confidence: 99%